Isotherm Studies for the Sorption of Metal Ions on to Peat - G. Mckay; B. Vong; J.F. Porter (Adsorption Science & Technology)
The adsorption of five single-component metal ions, namely, copper, cadmium, cobalt, nickel and zinc, on to peat has been studied. Equilibrium isotherms were measured and analysed using three methods: Langmuir, Freundlich and Redlich–Peterson. Overall the Langmuir equation gave the best fit based on a linear correlation coefficient. The Langmuir equation was used to determine the monolayer saturation capacity for each of the metals on peat. These sorption capacities are: cadmium, 99.47 μmol/g (11.18 mg/g) peat; cobalt, 446.93 μmol/g (26.34 mg/g) peat; copper, 198.31 μmol/g (12.60 mg/g) peat; nickel, 113.24 μmol/g (6.65 mg/g) peat; and zinc, 141.93 μmol/g (9.28 mg/g) peat.